1994
DOI: 10.1016/s0006-3495(94)80572-7
|View full text |Cite
|
Sign up to set email alerts
|

Solute effects on the colloidal and phase behavior of lipid bilayer membranes: ethanol-dipalmitoylphosphatidylcholine mixtures

Abstract: By means of the scanning differential calorimetry, x-ray diffractometry, and the dynamic light scattering, we have systematically studied the phase and packing properties of dipalmitoylphosphatidylcholine vesicles or multibilayers in the presence of ethanol. We have also determined the partial ternary phase diagram of such dipalmitoylphosphatidylcholine/water/ethanol mixtures. The directly measured variability of the structural bilayer parameters implies that ethanol binding to the phospholipid bilayers increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 16 publications
5
91
0
1
Order By: Relevance
“…GIXD experiments have shown that the effective area per head group decreases with an increase in ethanol concentration leading to a reduction of the chain tilt angle. The influence of ethanol on self-assembled aggregates of phospholipid molecules has been reported in [33][34][35][36][37][38][39]. In these investigations, lipid bilayers dispersed as unilamellar or multilamellar vesicles in an aqueous solution have been used.…”
Section: Influence Of the Head Groupmentioning
confidence: 99%
“…GIXD experiments have shown that the effective area per head group decreases with an increase in ethanol concentration leading to a reduction of the chain tilt angle. The influence of ethanol on self-assembled aggregates of phospholipid molecules has been reported in [33][34][35][36][37][38][39]. In these investigations, lipid bilayers dispersed as unilamellar or multilamellar vesicles in an aqueous solution have been used.…”
Section: Influence Of the Head Groupmentioning
confidence: 99%
“…The effect of ethanol on lipid systems came into existence during early 1990s. Vierl et al (1994) reported the investigative account of phase and packing properties of dipalmitoylphosphotidyl choline vesicles or multi-bilayers in the presence of ethanol, and then employment of high alcohol content was commenced by Touitou (Touitou, 1996;Touitou et al, 1997). The petite summary of numerous investigative literatures indicates that ethanol basically fluidizes and engorges the rigidly fixed lipid multilayer system of the stratum corneum lipids by reducing its T m , incorporation of high concentration of ethanol in ethosomes makes lipid vesicular membrane less densely crammed which provides warmness and malleability to them resulting in the formation of deformable and flexible vesicular system which could easily pierce through tiny openings formed in the disturbed SC lipids more deeply in contrast to other vesicular systems (Martin & Lloyd, 1992;Touitou, 1998).…”
Section: Alcohol and Effects Of Its Elevated Concentrationsmentioning
confidence: 99%
“…The earlier pressure results in augmentation of an ethanol dependent change of the area per molecule whereas latter leads to excessive swelling of phosphatidylcholine bilayers in the aqueous ethanol solutions. As a result of which ethanol can induce hydrocarbon inter-digitation and increases inter-membrane separation in the gel phase plus ethanol also widens the interface and by doing so increases the scope and series of the lipid head group solvation (Vierl et al, 1994). This feature of ethanol got a breakthrough in 1996 where it gets a platform of formulation consisting phospholipid, double distilled water (DDW) and propylene glycols (PG) etc, and the visage of ethosomes emerged (Touitou, 1996).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…To study the effect of these molecules on the properties studies on various model membranes have been carried out by various groups [66,[71][72][73][74][75][76]. These studies show that at low temperatures adding alcohol leads the formation of an interdigitated or L βI phase in stead of the commonly formed L c or L β (gel phases).…”
Section: Effect Of Alcoholmentioning
confidence: 99%